Development and external validation of a nomogram for predicting the conditional probability of survival after D2 lymphadenectomy for gastric cancer: A multicentre study. Issue 10 (October 2019) - Chen, Qi-Yue; Zhong, Qing; Wang, Wei; Desiderio, Jacopo; Liu, Zhi-Yu; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; et al.
Abstract: Background: Previous studies have elucidated that on average, long-term cancer survivors have better prognoses than newly diagnosed individuals. This study aimed to devise a nomogram to predict the conditional probability of cancer-specific survival (CPCS) in gastric cancer (GC) patients after D2 lymphadenectomy. Methods: Clinicopathological data for 2, 596 GC patients who underwent D2 lymphadenectomy in an Eastern institution (the training cohort) were retrospectively analysed. Cancer-specific survival (CSS) was predicted using Cox regression models. A nomogram was constructed to predict CPCS at 3 and 5 years post-gastrectomy. Two external validations were performed using a cohort of 2, 198 Chinese patients and a cohort of 504 Italian patients. Results: In the training cohort, the 5-year CPCS was 59.2% immediately post-gastrectomy and increased to 68.8%, 79.7%, and 88.8% at 1, 2, and 3 years post-gastrectomy, respectively. Multivariate Cox regression analyses showed that age; tumour site, size and invasion depth; numbers of examined and metastatic lymph nodes; and surgical margins were independent prognostic factors of CSS (all P  < 0.05) and formed the nomogram predictor variables. Internal validation showed that the conditional nomogram exhibited good discrimination ability at 3 and 5 years post-gastrectomy (concordance index, 0.794 and 0.789, respectively). External validation showed a 3- and 5-year concordance index of 0.788 and 0.785, respectively, in the Chinese cohort, and 0.792 and 0.787, respectively, in the Italian cohort. Calibration of the nomogram predicted that survival corresponded closely with actual survival. Conclusions: we developed a robust nomogram to predict CPCS after D2 lymphadenectomy for GC based on survival duration.